In vivo evidence for apoptosis in the bone marrow in systemic lupus erythematosus. Issue 8 (2nd February 2007) - Hepburn, Alastair L; Lampert, Irvin A; Boyle, Joseph J; Horncastle, Donna; Ng, W Fai; Layton, Mark; Vyse, Timothy J; Botto, Marina; Mason, Justin C
Abstract : An increase in leucocyte apoptosis and impaired clearance of apoptotic cells has been observed in patients with systemic lupus erythematosus (SLE). Apoptotic cells are likely to be a key source of autoantigens in SLE as they express many of the nuclear autoantigens (in surface blebs and apoptotic bodies) that are relevant to this disease. The clearance of apoptotic cells is usually a rapid process, such that few cells are usually seen in the extracellular environment in vivo . We report a case in which multiple apoptotic bodies were observed in the bone marrow of a patient with SLE that was complicated by an immune-mediated pancytopenia. We have subsequently examined the frequency of apoptotic cells, identified morphologically, and by caspase-3 staining in bone-marrow trephine samples taken from patients with SLE over a 10-year period of follow-up. A high proportion of bone marrows contained apoptotic debris. The novel demonstration of apoptotic bodies in vivo in patients with SLE is unusual and supports the notion that the marrow may be a target organ in the disease. Their abundance is also consistent with the hypothesis that normal clearance mechanisms are defective and/or overwhelmed in SLE.